Experimental Implementation for the Monitoring of Environmental Radiation by Radon in the Northern Macro-region of Perú. - Díaz, Félix (2023)
In the present work, we carry out the preparation and experimental implementation for the measurement and monitoring of environmental radon in the northern region of Peru, which according to geological studies, it is a region with uranium-rich soil. To carry out the monitoring, we use active detectors such as AlphaGUARD and Recon while using the CR-39 as a passive detector. Likewise, using a uranium ore (autunite) as a radon source in a controlled environment, we test diffusion chambers and analyze the correlation between the measurements of the active sensors.